2020
DOI: 10.29333/iji.2020.13118a
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perception Self-Esteem Physical Activity and Sedentary Behavior of Primary Greek- School Students: A Pilot Study

Abstract: The aim of the present study was to assess the level of self-perception, selfesteem, physical activity and sedentary behavior of primary school children between 10 and 12 years old in the city of Komotini (Rodopi East Greece, North), to investigate the correlation between the above parameters and to detect possible differentiation on each factor with regard to the age and gender of the children. The sample of the survey consisted of 153 students from five public primary schools. The students were divided accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
3
0
4
Order By: Relevance
“…Physical activity was confirmed to be a positive predictor of self-perception, such that higher levels of physical activity tend to lead to better self-perception, with a corresponding improvement in prosocial behavior, consistent with previous studies [11,34]. Previously, physical activity has been positively associated with the physical and mental health of college students, affirming the notion that engaging in regular physical activity is a healthful practice.…”
Section: The Mediating Role Of Self-perceptionsupporting
confidence: 87%
See 1 more Smart Citation
“…Physical activity was confirmed to be a positive predictor of self-perception, such that higher levels of physical activity tend to lead to better self-perception, with a corresponding improvement in prosocial behavior, consistent with previous studies [11,34]. Previously, physical activity has been positively associated with the physical and mental health of college students, affirming the notion that engaging in regular physical activity is a healthful practice.…”
Section: The Mediating Role Of Self-perceptionsupporting
confidence: 87%
“…It has been suggested that increasing one's self-perception may lead one to reflect on their own values and ideals, and such reflections may promote prosocial behaviors [8]. Some studies have shown that highly active college students self-report having better views of themselves than students with a low level of physical activity [9][10][11][12]. Some studies have found that physical activity led adolescents to have a better self-concept, which improved their confidence in establishing good interpersonal relationships with peers and teachers.…”
Section: Introductionmentioning
confidence: 99%
“…There is is a significant relationship between physical activity and self-esteem among participants [64]. Positive results were found on the effect of physical activity and self esteem [65], [66] among students who participated in the research.…”
Section: Resultsmentioning
confidence: 98%
“…En este sentido, los estudiantes que practican AF de manera regular muestran mejor autoconcepto que las personas que tienen un estilo de vida sedentario (Batsiou et al, 2020), por lo que se supone que, tanto el nivel de AF como el tipo de deporte practicado, pueden actuar como mediadores en el desarrollo del autoconcepto (Babic et al, 2014), estando especialmente relacionados con el autoconcepto físico (Duclos-Bastías et al, 2022). En línea con lo anterior, la práctica de AF regular puede favorecer la percepción que tiene un individuo sobre su aspecto físico al mismo tiempo que genera beneficios a nivel fisiológico, cognitivo y social, y, por tanto, mejora el autoconcepto general (Chacón-Cuberos et al, 2020).…”
Section: Introductionunclassified